Factors Affecting Financing Distribution of Sharia Commercial Banks in Indonesia - Putri, Tsamara Nadya Cantika; Sukmaningrum, Puji Sucia (Universitas Pendidikan Indonesia, 2023)
This study aims to analyze the effect of inflation, economic growth, interest rates, asset quality, capital adequacy, and profitability on the distribution of Islamic commercial bank financing in Indonesia (2014 – 2019) partially or simultaneously. In this study, the variables used are financing distribution as measured by FDR, profitability as measured by Bank ROA, inflation, economic growth as measured by GDP, interest rate as measured by the BI Rate or BI7DRR, and capital adequacy as measured by CAR and asset quality measured by the NPF. The quantitative approach used with panel data regression method with the analysis tool Eviews 10. This study uses secondary data derived from the annual financial statements of Islamic commercial banks in Indonesia. Sampling was carried out using purposive sampling with several criteria, resulting in a sample of 10 BUS in Indonesia. The results show that the interest rate and asset quality partially affect the distribution of financing with a significant positive. In contrast, economic growth, inflation, capital adequacy, and profitability do not significantly affect the distribution of BUS financing in Indonesia. Simultaneously, inflation, economic growth, interest rates, capital adequacy, asset quality, and profitability significantly impact the distribution of BUS financing in Indonesia.